Recognising and healing emotional wounds of child labourers: call to action based on the evidence and stakeholder views from India and Nepal. (May 2022) - Kaur, Harleen; Duncan, Kathleen; Dhakal, Sandesh; Sharma, Narayan; Niraula, Shanta; Pandey, Rakesh; Kumari, Veena; Lau, Jennifer Y. F.; Singh, Tushar
Abstract : Child labourers are at risk of poorer mental health and once rescued require urgent mental health interventions to ameliorate the long-term impact. In our review, only two published scientific studies evaluated custom-made interventions; other programmes were obtained from non-governmental organisations (NGOs), which need rigorous trial evaluation. We also sought the viewpoints of stakeholders working directly with rescued young people, as well as consulting young people with lived experiences of child labour. We propose that psychoeducational interventions aimed at employees working directly with young people could represent a fruitful approach for low- and middle-income countries in the Asia-Pacific region but also more generally.